ADOPSI PENGGUNAAN E-COMMERCE TERHADAP KINERJA UMKM (Pada Usaha Mikro, Kecil, dan Menengah di DKI Jakarta) - Ananda Putri Harfie; Anies Lastiati (Universitas Budi Luhur, 2022)
This study was conducted to examine whether each of the technological, innovation, and environmental factors that influence the tendency of MSMEs to adopt e-commerce and the impact of e-commerce adoption on MSME performance. Data was collected using a questionnaire with the selection of samples using the purposive sampling method, namely SMEs in DKI Jakarta. The analysis used is descriptive analysis, outer model analysis, inner model analysis, and hypothesis testing. The test results show that each of the technology, innovation, and environmental factors has a positive effect on e-commerce adoption and e-commerce adoption has a positive effect on the performance of MSMEs in DKI Jakarta. The distribution of the questionnaire uses a technology-based platform (Instagram and Email) and focuses on the age group of 20 to 25 years. This study did not conduct in-depth research on each application of the variables tested. With this research, MSMEs are more aware and concerned about the importance of e-commerce in their business because nowadays people prefer to shop online.